O comportamento verbal musical: conceitos e dados experimentais - Machado, Alex Roberto (2014)
Any movement produced by the body can be verbal towards Skinner. This work supports the idea that music is a special human verbal behavior. For this defense three articles focus were produced in the discussion of the concept of communication in music, musical topography of stimulus and empirical demonstration of correspondence between the composer and the listener. The first article is theoretical and aimed to approximate the behavior-analytic concepts of Linguistics and Music regarding communication. Every field of knowledge was presented separately and then points were signalized intersection between the concepts of each area. The second article was also theoretical and proposed a taxonomy of topographical stimuli, aiming to help their discrimination by behavior analysts. The stimuli were classified into five levels: (1) location; (2) sensing system; (3) objectivity / arbitrariness; (4) means; and (5) mode. Were presented and discussed examples for each category. The third article was empirical and aimed to describe the relationship between musical stimuli with different properties modified, the judgment of emotions from different populations. To achieve this, three graduate students in music produced four pieces that sinalizassem emotions (happiness, sadness, tranquility / peace, anger / fear). Then, 46 psychology students, lay in music, the 12 songs heard and judged emotionally. A university professor of music also judged the excerpts, some discriminating variables of which the different levels of correspondence were found function. Each article has fostered an argument in favor of the thesis: the first article indicated the lack of a musical analogue to the grammatical linguistic categories, like nouns and adjectives; the second article indicated topographical conditions of music, distinguishing it from other verbal; the third article indicated as verbal musical episode allows a plurality of "understandings" possible by the listener. The articulation of these arguments elucidated different aspects that corroborate the assertion that music is a special verbal behavior.